The Effect of Fracture Strength of Composite Materials with the Addition of Pineapple Leaf Fiber - Nusyirwan Adnan (Jurnal Inovasi Teknologi, 2025)
Composite materials with unsaturated polyester matrix reinforced with natural fibres were developed to make biodegradable composite materials so that the waste does not damage the environment. Regarding mechanical strength, natural fibre-based composites are still lower in mechanical strength than composite materials with synthetic fibre reinforcement. These weaknesses include easy cracking when hit because they are brittle and have a small plastic deformation area. Some actions that will be carried out in this study are the addition of pineapple fibres with unsaturated polyesters that can form composites that are resistant to cracking. The addition of pineapple fibers to unsaturated polyesters up to 20% can have the highest fracture strength with a value of K1C = 1.733 MPa.m0.5, whereas pure unsaturated polyester without a mixture of pineapple fibres only has a fracture strength of K1C = 0.779 MPa.m0.5. From the results of the study, the addition of pineapple fibres can increase the fracture strength of polyester materials by 222.47%.